Coupling the Effect of Wind and Pavement Dynamics in Longitudinal Dynamics of Twin Track Vehicle - Dr. K M Jagadeesha, Mr. Gopalareddy (International Journal of Advanced Science and Technology, 2020)
Vehicle Performance, stability and control is not only depending on vehicle parameters like center of gravity location, vehicle speed and tire-parameters, it of an extent influences by many other parameters like wind, pavement and driver inputs. The wind–pavement-vehicle dynamics analysis plays a dominant role in Vehicle Performance, stability and control and it has been considerably developed in the past decades. In this work, much attentiveness hasbeen agreed towards the effect of aerodynamic forces on acceleration and rakingperformance, on the twin track vehicles, comparing the acceleration and braking performance of two different models under different conditions (considering the lift and neglecting the lift) by considering the coefficient of adhesion, aerodynamics characteristics and location of center of gravity.For the purpose of study two different car models were considered namely model-1 and model-2 and they were modeled using modeling software CATIA V5. Attention is given only to the external design of the cars, while the interiors were not modeled. Further, analysis has been carried out using ANSYS-Fluent to determine the aerodynamic characteristics like drag coefficient (Cd) and coefficient of lift (Cl). With the help of flatbed tire testing machine, the coefficient of adhesion has been experimented on various pavement types and conditions by changing the inflation pressure and vertical load on tires.In the results it has been observed that model-1 has better acceleration and braking performance than the model-2 comparatively. Acceleration and braking performance are more in the condition of neglecting the lift and comparatively less in the condition of considering the lift. Acceleration of ground vehicles decreases with increase in lift force. Also, the braking performance of vehicles decreases with increase in lift force.